Marcel Wanders : behind the ceiling. - Klanten, Robert, 1964-; Mollard, Adeline, ....-; Moreno, Shonquis, ....- (Berlin : Gestalten, 2009)
Marcel Wanders is the highly anticipated first monograph on one of the most influential, prolific and celebrated international designers today. Wanders' designs are characteristically buoyant and imbued with his signature irony and quirky dry wit that evoke imagination; nevertheless all of the featured examples of furniture, lighting, interiors, textiles, tableware, decorative porcelain and ceramic vases as well as his personal art editions are unpretentiously urbane. This book showcases his body of work and stellar career through stunning photography, sketches, copious texts and quotes from the designer himself, offering a first-hand account of Wanders' irresistible universe.
Keywords: Ontwerpers